Предмет: Алгебра,
автор: Iskander666
пожалуйста помогите мне пожалуйста
Приложения:
Ответы
Автор ответа:
1
1. (а-b)*(a+b)
2.(2a)^2+2*2a*3b+(3b)^2=(4a)^2+12ab+(9b)^2
3.a^2-2a*4b+(4b)^2=a^2-8ab+(16b)^2
4.(3a^2)^3+3*(3a^2)^2*b+3*(3a)^2*b^2+b^3=(27a)^6+3*(9a)^4*b+(9a)^2*b^2+b^3=(27a)^6+(27a)^4*b+(9a)^2*b^2+b^3
5.(2a^4)^3-3*(2a^4)^2*3+3*(2a)^4*3^2-3^3=(8a)^12-3*(4a)^8*3+3*(2a)^4*9-27=(8a)^12-(36a)^8+(54a)^4-27
6.(a-b)*(a^2+ab+b^2)
7.(a+b)*(a^2-ab+b^2)
Iskander666:
это вы преобразовали в многочлены?
Похожие вопросы
Предмет: Алгебра,
автор: rarvooo08
Предмет: Математика,
автор: theatremylenko
Предмет: Физика,
автор: Annn1333
Предмет: Геометрия,
автор: Lina20102003
Предмет: История,
автор: Zadeta